Can Biogeochemical Tracer Observations Constrain Southern Ocean Diapycnal Mixing Rates? - Ellison, Elizabeth; Mazloff, Matthew; Mashayek, Ali (American Geophysical Union (AGU), 2025)
Publication status: Published Funder: Engineering and Physical Sciences Research Council; doi: http://dx.doi.org/10.13039/501100000266 Funder: Office of Nuclear Energy; doi: http://dx.doi.org/10.13039/100006147 Funder: National Aeronautics and Space Administration; doi: http://dx.doi.org/10.13039/100000104 Abstract Direct observations of background diapycnal mixing rates in the Southern Ocean (SO) are limited spatially and temporally, making the choice of an appropriate value to parameterize this mixing in Earth system models a challenge. However, the deployment of Argo floats throughout the SO has provided an extensive range of observations of both physical and biogeochemical parameters. We use an ocean state estimate run with various background diapycnal mixing coefficients to assess if biogeochemical tracer observations can be used to better constrain SO diapycnal mixing rates. We find that vertical tracer distributions in the SO are highly sensitive to the rate of background diapycnal mixing and can provide an upper limit on background mixing rates. This demonstrates the importance of biogeochemical tracer observations throughout the full depth of the water column to validate ocean models.